The correlation of the modulation complexity score (MCS) with the number of segments and local gamma passing rate for the Intensity Modulated Radiation Therapy (IMRT) treatment planning delivery - Omar Najah Jubbier; Ali Majeed Hassan; Siham Sabah Abdullah; Haydar Hamza Alabedi; Nabaa Mohammad. Alazawy; Mustafa Jabbar Al-Musawi (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the modulation complexity scores across treatment sites, and to examine their connection with monitor unit, segment number and global and local gamma passing percentage. Method: The cross-sectional study was conducted at the Baghdad Centre for Radiation Therapy and Nuclear Medicine, Baghdad Medical City, Baghdad, Iraq, from May 2021 to February 2022. Included were 34 patients, with the age range between 20 – 50 years, subjected to intensity-modulated radiation therapy for head and neck tumours in group A or pelvic tumours in group B. Treatment planning was done using Monaco 5.1, and radiotherapy was done using Synergy linear accelerator. Modulation complexity scores were calculated using MATLAB 2019a. Data was analysed using SPSS 24. Results: Of the 34 patients, 22(64.7%) were in group A; 12(54.5%) males and 10(45.5%) females. There were 12(35.3%) patients in group B; 8(66.7%) females and 4(33.3%) males. The number of segments was greater in group B than group A. A modest positive linear association was seen in group A, demonstrating that an increase in segment numbers resulted in a rise in modulation complexity score (R2=0.0244). Group B tumours had inverse negative linear correlation (R2=0.0189). As the complexity of plans increased in group A, local gamma passing percentage decreased (R2=0.0452). Group B showed a slight negative connection with modulation complexity score (R2=0.0622). Conclusion: The modulation complexity score may be used to provide a simple prediction for pre-treatment verification, and it may also serve as a simple quality assurance tool for intensity-modulated radiation therapy plans. Key Words: Monaco, Nuclear, Pelvic, Head and Neck